The Concept of Religious Moderation in Islamic Education: A Study of the Thought of Contemporary Ulama - Abdul Wahab (ANWARUL, 2025)
Religious moderation has emerged as a strategic imperative in Islamic Education (Pendidikan Agama Islam, PAI) amid rising concerns over radicalism, intolerance, and social polarization in Indonesia. This study critically examines the concept of religious moderation from the perspectives of contemporary Muslim scholars and explores its relevance for the development of PAI. Adopting a library research approach, the study employs descriptive-analytical and interpretative methods to review the works of Yusuf al-Qaradawi, Quraish Shihab, Fazlur Rahman, and Ali Jum'ah. The analysis reveals that these scholars conceptualize religious moderation through core values such as justice, tolerance, balance, and deliberation, positioning them as essential principles for religious life. These values are particularly relevant for integration into PAI curricula to foster inclusive, dialogical, and socially harmonious student character in Indonesia’s multicultural context. However, implementation faces notable challenges, including an overly cognitive curriculum, insufficient teacher preparedness, and the widespread dissemination of intolerant ideologies via digital media. The study concludes that religious moderation has significant potential to enhance PAI’s role in cultivating a moderate Muslim generation, contingent upon curriculum reform, teacher capacity development, and stronger alignment between educational policy and societal values. Theoretically, the study contributes to mapping contemporary Islamic thought on moderation; practically, it offers strategic recommendations for embedding these principles into Islamic education.